2010
DOI: 10.1016/j.ijantimicag.2010.08.010
|View full text |Cite
|
Sign up to set email alerts
|

The Nationwide Austrian Aspergillus Registry: a prospective data collection on epidemiology, therapy and outcome of invasive mould infections in immunocompromised and/or immunosuppressed patients

Abstract: A prospective, observational, multicentre study was performed to assess the incidence, diagnosis, epidemiology and outcome of invasive mould infections (IMIs) reported to the Nationwide Austrian Aspergillus Registry. In total, 186 cases were recorded, corresponding to an annual incidence of 42 cases/1000 patients at risk or 2.36 cases/100000 inhabitants. Patients with acute myelogenous leukaemia (34%) and lung transplant recipients (17%) are currently at highest risk for IMI, followed by a mixed population wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 37 publications
6
59
1
1
Order By: Relevance
“…[1][2][3][4][5] Voriconazole treatment appears to be independently associated with improved survival through a decrease in IAattributable mortality. 1,2,4,6,7 These findings support other available evidence in legitimizing the universal recommendation of voriconazole as a first-line IA treatment in hematologic and other immunocompromised patients. [8][9][10][11] Most studies have examined 3-, 4-or 6-month survival rates of HSCT recipients with IA, but immunosuppression is a persistent problem in this patient population.…”
Section: Introductionsupporting
confidence: 81%
“…[1][2][3][4][5] Voriconazole treatment appears to be independently associated with improved survival through a decrease in IAattributable mortality. 1,2,4,6,7 These findings support other available evidence in legitimizing the universal recommendation of voriconazole as a first-line IA treatment in hematologic and other immunocompromised patients. [8][9][10][11] Most studies have examined 3-, 4-or 6-month survival rates of HSCT recipients with IA, but immunosuppression is a persistent problem in this patient population.…”
Section: Introductionsupporting
confidence: 81%
“…Multiple prophylactic azole drugs m.R. ananda-Rajah et al 462 haematologica | 2012; 97(3) 4 Pulmonary lesions treated for suspected invasive fungal infection but not meeting consensus criteria. 11 5 Comparing discontinuation in the itraconazole vs. voriconazole+posaconazole groups combined.…”
Section: Discussionmentioning
confidence: 99%
“…EAFT was higher in the combined fluconazole/itraconazole compared to the voriconazole/ posaconazole groups (31% vs. 8.5%, P<0.001) as were pulmonary lesions on computed-tomography treated for suspected IFD but not meeting criteria for possible-IFD (10% vs. 4 …”
Section: Plasma Levels Of Itraconazole Voriconazole and Posaconazolementioning
confidence: 95%
See 1 more Smart Citation
“…Fungi of the families Saksenaceae and Syncephalastraceae are uncommon pathogens and are typically restricted to tropical areas, affecting immunocompetent hosts (Petrikkos et al, 2012). Whereas the exact incidence of mucormycosis is unclear and probably underestimated, an Austrian observational study recently reported 28% of their collected invasive mould infections were caused by Mucorales, equal to 1.2% of at-risk patients (Perkhofer et al, 2010). Other studies reported up to 13% incidence in high-risk patients, and risk of IFD was mainly associated with haematological malignancies and diabetes mellitus (Petrikkos et al, 2012).…”
Section: Introductionmentioning
confidence: 99%